Thermal Conductivity Enhancement of TiO2 Nanofluid in Water and Ethylene Glycol (EG) Mixture - K., Abdul Hamid; Azmi, W. H.; R., Mamat; N. A., Usri (National Institute of Science Communication and Information Resources, 2016)
The need to study nanofluid properties has increased over these past centuries in order to provide better understanding on nanofluid thermal properties and behaviour. Due to its ability to improve heat transfer compared to conventional heat transfer fluids, nanofluids as a new coolant fluid have widely been investigated. This study presents the thermal conductivity enhancement of titanium dioxide (TiO2) nanoparticles dispersed in mixture of water and ethylene glycol (EG). The nanofluids have been prepared for volume concentrations from 0.5 to 1.5%. The thermal conductivity measurement of the nanofluid has been performed using KD2 Pro Thermal Properties Analyzer at working temperatures of 30 to 80 °C. The measurement gives 15.35% maximum enhancement of thermal conductivity at 1.5% volume concentration and temperature of 60 °C. The results show that the thermal conductivity increases with the increase of nanofluid concentration and temperature. Also, the nanofluids provide enhancement in thermal conductivity compared to their base fluid of a water/EG mixture in 60:40 ratio. Therefore, the addition of TiO2 nanoparticles dispersed in the base fluid of a water and EG mixture will enhance the effective thermal conductivity of the nanofluid. The new thermal conductivity correlation of TiO2 nanofluids is developed for a wide range of temperatures and concentrations with maximum deviation of 4.65% and average deviation of 1.37%.